Bioremediation of Fluorophenols by Glycosylation with Immobilized Marine Microalga Amphidinium Crassum - Kei Shimoda; Hiroki Hamada (SAGE Publishing, 2010)
Fluorophenols are used as agrochemicals and released into environment as pollutants. Cultured marine microalga Amphidinium crassum ( Gymnodinium ) glucosylated 2-fluorophenol ( 1 ), 3-fluorophenol ( 2 ), and 4-fluorophenol ( 3 ) to the corresponding β-D-glucosides, ie, 2-fluorophenyl β-D-glucoside ( 4 , 60 μg/g cells), 3-fluorophenyl β-D-glucoside ( 5 , 20 μg/g cells), and 4-fluorophenyl β-D-glucoside ( 6 , 40 μg/g cells). On the other hand, 2-, 3-, and 4-fluorophenols were efficiently converted by immobilized A. crassum in sodium alginate gel to give their β-D-glucosides in higher yields ( 4 : 140 μg/g cells; 5 : 60 μg/g cells; 6 : 100 μg/g cells). In repetitive batch use, the immobilized cells of A. crassum maintained the potential for the glucosylation of the substrate fluorophenol after 5 times of usage.